A rapid degreasing method for ceramic injection molding blanks

By using gradient porous ceramic membrane for siphon degreasing, the problems of long degreasing time and unstable product quality of ceramic injection molded blanks are solved, and an efficient and stable degreasing process is achieved, which is suitable for large-scale production.

CN118388259BActive Publication Date: 2024-12-13CHENGDU JINGYU ZHIXIN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410487643.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2024-12-13
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

The existing degreasing process of ceramic injection molded blanks has problems such as long degreasing time, high cost, and unstable product quality. Especially the degreasing process caused by the powder burial process takes a long time, powder adheres to the surface of the blank, and is highly uncontrollable. , affects production efficiency and product quality.

Method used

The template method is used to prepare gradient porous ceramic membranes with accurate and controllable pore sizes, and the matching stage is made through mechanical processing, combined with TG-DSC analysis to design degreasing process parameters, and the gradient porous ceramic membrane is used for siphon degreasing, which avoids the inadequacy of the powder buried process. .

Benefits of technology

It significantly shortens the degreasing time, improves production efficiency, solves the problem of powder adhesion on the surface of the blank, ensures the consistency of the degreasing process and product quality, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118388259B_ABST
    Figure CN118388259B_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapid degreasing of ceramic injection molded blanks, comprising: preparing a porous ceramic membrane material with precisely controllable pore size and gradient pore size distribution by a template method; accurately making a gradient porous ceramic membrane stage for carrying the injection molded blank according to the three-dimensional appearance of the injection molded blank; then placing the injection molded blank on the processed stage, and then matching the precisely processed gradient porous ceramic membrane above the blank. The ceramic injection feed is subjected to TG-DSC analysis, and accurate degreasing process parameters are designed according to the TG-DSC analysis results. The invention adopts a gradient ceramic membrane with a multi-level pore size vertical design distribution as a siphon in the degreasing process, the pore size of the ceramic membrane is precisely controlled, and the pore size presents a gradient distribution, which greatly accelerates the siphoning process and decomposition and diffusion process of organic matter and greatly improves the degreasing efficiency. The time required for degreasing is greatly shortened, and at the same time, the yield rate of the degreasing blank and the consistency of the degreasing blanks in the same batch are improved, which is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of precision ceramics, and relates to a method for rapid degreasing of ceramic injection-molded blanks, and specifically to a precisely designed gradient porous ceramic membrane and a method for rapid degreasing of injection-molded precision ceramic blanks based on a ceramic membrane. Background Art

[0002] The shapes of precision parts are very complex and the requirements for precision are very high. The cost of manufacturing precision parts by mechanical processing is very high. Ceramic injection molding is a precision molding technology that is particularly suitable for ceramic parts with complex shapes, small sizes, precision, and thin walls. It is an important branch of powder injection molding technology and one of the important directions for the development of advanced ceramic manufacturing industry. The blanks prepared by ceramic injection molding method are composed of ceramic powder particles, binders and various additives. Ceramic injection blanks need to undergo subsequent degreasing / debinding, high-temperature sintering densification and subsequent precision machining processes to prepare precision parts that meet performance requirements. Conventional thermal degreasing processes have very slow heating rates, very long degreasing processes, and low product production efficiency; the equipment costs and environmental costs required for catalytic degreasing methods and solvent extraction degreasing methods are very high, and are not suitable for large-scale production processes.

[0003] High-efficiency, low-cost and large-scale degreasing technology for ceramic injection blanks is a key technology that needs to be broken through. High-efficiency and low-cost degreasing technology is the key to significantly reducing the manufacturing cost of injection-molded precision ceramic parts and expanding the scope and scenarios of product applications. The design and selection of degreasing methods and processes are mainly determined by the system and composition of the binder. Paraffin wax (PW) has the advantages of low melting point, low cost and wide application range. Paraffin wax, which is commonly used as a binder, has a melting point of 55-65°C and is generally used as the main component of the binder. Polypropylene (PP) is a thermoplastic polymer with tough mechanical properties, a melting point of 160-166°C, and strong adhesion. It can effectively improve the strength of the injection blank and is generally used as a component of the binder. Stearic acid (SA), also known as octadecanoic acid, has the chemical properties of general carboxylic acids and is a white waxy transparent solid or a slightly yellow waxy solid. As a dispersant, stabilizer and lubricant in the binder system, it is added in small amounts.

[0004] For the injection molding technology of ceramic powders, the basic composition of the binder system most used in industrial production is PW-PP-SA. For this component system, the mainstream degreasing method is thermal degreasing. The principle of thermal degreasing is to gradually increase the temperature of the injection blank by heating, so that the organic binder in the blank undergoes processes such as softening, melting, volatilization, cracking, oxidative decomposition, and diffusion. During the heating and insulation process, the binder gradually changes from the solid phase to the liquid phase and the gas phase, and is gradually removed from the blank, and finally the degreasing process is completed. The advantage of the thermal degreasing method is that the required equipment is simple and has a wide range of applications. Its disadvantage is that the degreasing speed is very slow, and the degreasing rate is generally 0.1 to 1 mm / h. Unreasonable process control during the degreasing process often leads to bubbling and cracking of the blank, resulting in the scrapping of the blank.

[0005] Another degreasing method suitable for the PW-PP-SA system is siphon degreasing. The principle of siphon degreasing is to bury the injection molded blank in a ceramic powder with fine particles, large specific surface area and strong adsorption capacity. The particles used for the powder embedding process are generally selected from alumina particles that have been calcined at high temperature. The buried powder particles are required to be fine and the particle size distribution is controlled at 1 to 5 μm. Due to the external pressure, capillary channels are formed between the particles. During the heating process, the liquid phase produced by the melting of the binder in the blank can be sucked by these capillary channels, and the volatile gases generated during the heating process of the binder can be adsorbed by the capillary channels. The advantage of the siphon degreasing method is that the degreasing speed is fast and the degreasing time can be saved. The disadvantage is that fine powder is easily adhered to the surface of the blank and impurities are introduced, and an additional fine powder removal process is required.

[0006] In practical applications, the combined use of thermal degreasing and siphoning methods can shorten the degreasing time, thereby increasing the degreasing rate and obtaining a degreasing blank with a high binder removal rate. In 2007, Qiao Bin et al. (Study on the siphon-thermal two-step degreasing process of metal injection molding blanks [J]. Hot Working Technology, 2007, 36 (13): 54-55, 58.) conducted a study on the degreasing process of injection molded metal blanks by using a siphon-then-thermal degreasing process. The binder system used was PW-LDPE-SA, where LDPE refers to low molecular weight polyethylene. The results showed that the siphon-thermal two-step degreasing method can greatly shorten the degreasing time to about 10 hours. The literature did not specify the siphon powder used. In 2023, patent CN117362029A disclosed a full-heat degreasing process based on buried powder. The binder system is PW-PE. The powder used in the buried powder process is C / Al2O3 mixed powder obtained by mixing nano-scale carbon powder and submicron alumina powder in a certain ratio. The degreasing time is about 18 hours, and the degreasing rate reaches more than 99%. This process consumes a lot of buried powder and is not suitable for mass production.

[0007] The buried powder thermal degreasing process disclosed in the prior art has the following technical difficulties:

[0008] (1) The powder embedding process makes a large number of injection blanks densely distributed in the compacted fine-grained powder, blocking the circulation of air. The decomposition process of organic matter needs to be controlled very slowly, and the degreasing process takes a long time.

[0009] (2) The powder embedding process cannot solve the problem of powder adhering to the surface of the blank during the degreasing process. Generally, a special surface powder removal process is required after degreasing, which increases costs and reduces product quality and yield.

[0010] (3) The existing powder embedding process regulates the capillary channels between particles by adjusting the grading of powder particle size and external pressure. This process is highly uncontrollable, resulting in a large degree of uncontrollability in the degreasing process. The degreasing effects of different batches also vary to a certain extent, which seriously affects product quality.

[0011] (4) The processes of arranging the defatted blanks, embedding the powder and pressing the powder require a lot of manpower and time, and the production efficiency is low, which directly leads to an increase in the cost of the finished product. Summary of the invention

[0012] In view of the shortcomings of the prior art, the present invention provides a precisely designed porous ceramic membrane material and a rapid degreasing process for ceramic injection molded blanks. The present invention adopts the following technical solutions:

[0013] A rapid degreasing method for a ceramic injection molded blank, comprising:

[0014] S1. A template method is used to prepare porous ceramic membrane materials with precisely controllable pore size and pore size gradient distribution.

[0015] like Figure 1 As shown in the figure, a single-layer through-hole ceramic membrane prepared by the template method is shown. The figure shows the cross-sectional morphology of the ceramic membrane. The material of the ceramic membrane is alumina. From the photo, it can be seen that the pore size of the ceramic membrane is uniform and most of the pores are connected, which can quickly absorb and discharge the decomposition gas generated during the degreasing process. Figure 2 As shown in the figure, the physical picture of the gradient porous ceramic membrane prepared by the template method and the stacking drying and sintering method. The figure shows the cross-sectional morphology of the gradient porous ceramic membrane composed of three layers of porous ceramic membranes. It can be seen that the pore size gradually transitions from 1 to 1.5 mm to 5 to 7 mm, and the pores are connected. This gradient porous structure will be very beneficial to the degreasing siphon process and gas discharge process.

[0016] S2. Make spatial modeling for the three-dimensional appearance of the injection blank. According to the appearance of the blank, a loading platform for the injection blank with a size and shape that precisely matches the blank is dug out by mechanical processing on the gradient porous ceramic membrane prepared in S1. Then, the injection blank is placed on the processed loading platform, and then the gradient porous ceramic membrane is covered on top of the blank.

[0017] like Figure 3 As shown, a schematic diagram of the gradient porous ceramic membrane structure is shown. From the figure, it can be seen that the gradient ceramic membrane is composed of three layers of porous ceramics, the top membrane layer has the smallest pore size, the middle layer is the transition layer, and the bottom membrane layer has the largest pore size. Figure 4 The schematic diagram of the stage is processed based on the gradient porous ceramic membrane structure according to the three-dimensional appearance of the injection blank. The injection blank has regular tooth-like protrusions, and a precise stage structure needs to be processed on the ceramic membrane structure. Since the single size of the injection blank is small, multiple stages can be processed on a ceramic membrane structure. According to the structure of the upper surface and the structure of the lower surface of the injection blank, the stages with matching shapes are processed respectively. The processing of the stage is limited to the ceramic membrane layer with the smallest pore size to ensure that the surface of the injection blank directly contacts the membrane layer with the smallest pore size of the ceramic membrane. Figure 5 The schematic diagram of the spatial structure of the injection molded part to be degreased is shown. Figure 5 As shown in the figure, since the spatial structure of the stage is precisely processed and prepared according to the appearance of the injection blank, the outer surface of the injection blank will fit very closely with the ceramic membrane stage. This will accelerate the siphon degreasing process and ensure that the injection blank will not be deformed or damaged during the degreasing process. After the degreasing process is completed, the injection blank can be removed very conveniently.

[0018] S3. Carry out TG-DSC analysis on ceramic injection feed. According to the TG-DSC analysis results, design precise degreasing process parameters and greatly improve degreasing efficiency.

[0019] like Figure 6 The TG-DSC test results of the injection feed are shown in Figure 1. The basic composition of the injection feed is 80wt% ZTA ceramic powder and 20wt% binder. The composition of the binder is 78% paraffin, 15% polyethylene glycol, 5% dibutyl phthalate, 1% stearic acid and 1% oleic acid. The preparation of the feed is described in detail in Example 1. Figure 6 The TG-DSC test results of the component feed are given, and the test atmosphere is static air. According to the mass loss data and heat absorption or heat release data during the heating process (room temperature ~ 600oC), a reasonable temperature curve for the degreasing process is formulated.

[0020] S4. Set the temperature curve of the debinding furnace according to the designed debinding process parameters to quickly complete the debinding process in an air atmosphere.

[0021] like Figure 7 As shown, according to the actual conditions of the embodiments and comparative examples, different temperature curves of the degreasing process are set, and the shortest process curve for the degreasing heating and insulation period is 1180 min, and the longest is 3440 min.

[0022] S5. After degreasing, the injected ceramic blank is taken out, the degreasing blank is weighed, its surface characteristics are observed and recorded, and the degreasing effect is evaluated.

[0023] Figure 8 The picture shows the actual object before degreasing of the injection blank. Fig. 9 The degreasing effect is evaluated based on whether a large amount of powder adheres to the surface, whether blistering, cracks and other surface defects occur, and whether the blank is cracked or damaged.

[0024] Furthermore, the porous ceramic membrane material with pore size gradient distribution in step S1 is prepared by the following method:

[0025] (S1-1) Preparation of alumina ceramic slurry: 99 parts (mass ratio) of α-alumina powder and 1 part (mass ratio) of magnesium oxide powder are placed in the ball mill of a horizontal ball mill, with alumina ceramic balls as grinding media and pure water as dispersion medium. The mass ratio of material, balls and water is 1:5:2, 0.1% triethanolamine is added according to the mass of the powder, the speed of the ball mill is set to 60r / min, and the ball mill is performed for 24 hours to obtain a slurry for use.

[0026] (S1-2) Organic template pretreatment: Put the polyurethane foam into a 10% by mass NaOH solution, heat it in a 60°C water bath and soak it for 4 hours, rub it repeatedly, wash it with clean water, and put it in a drying oven at 60-110°C to dry it for 8-12 hours. The pore size and porosity of the polyurethane foam board are designed and selected according to actual conditions.

[0027] (S1-3) Dipping and slurrying: The pretreated polyurethane foam is placed in the ceramic slurry prepared in step (S-1) for dipping and slurrying, and the excess ceramic slurry is removed by a roller press.

[0028] (S1-4) Lamination and drying: Lay the impregnated polyurethane foam flat and stack it, apply a small amount of carbon powder particles between the layers, put it in an oven, and dry it at 80-110° C. for 8-12 hours;

[0029] (S1-5) debinding: placing the laminated green body in a debinding furnace, heating the temperature to 500-650°C at a heating rate of 2°C / min and keeping the temperature for 1-2h;

[0030] (S1-6) Sintering: The debinded green body is placed in a kiln and heated to 1400-1450°C at a heating rate of 5°C / min, kept at this temperature for 1-2 hours, and then cooled naturally.

[0031] Furthermore, the loading platform for the injection blank in step S2 is manufactured by the following method:

[0032] The fired samples of ceramic membranes can be used for degreasing process after size cutting, precision machining and surface treatment. The pore size range of ceramic membranes is 0.1mm~1.2mm, and the pore size gradient is designed as the innermost pore size is about 0.1~0.2mm, the middle pore size is 0.3~0.6mm, and the outermost pore size increases to 0.8~1.2mm; the membrane thickness is designed according to the thickness of the blank, which is generally 6~12 times the thickness of the blank.

[0033] Furthermore, the degreasing process parameters in S4 include:

[0034] Degreasing temperature Degreasing time RT~120℃ 60min 120℃~240℃ 240min 240℃~300℃ 600min 300℃~460℃ 320min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0035] Furthermore, the evaluation of the degreasing effect in S5 includes indicators such as degreasing rate, surface flatness of the blank, cracks, and blistering; wherein:

[0036] The formula for calculating the degreasing rate is: P = (m1-m2) / m×100%;

[0037] In the formula, m1 is the mass of the ceramic injection blank, in g; m2 is the mass of the ceramic degreased blank, in g; m is the mass of the binder contained in the ceramic injection blank, in g. In this technical solution, the value of m is 20.0.

[0038] In summary, compared with the existing degreasing technology, the technical solution of the present invention has the following outstanding advantages:

[0039] 1. A gradient ceramic membrane with a multi-level aperture vertical design distribution is used as a siphon in the degreasing process. The aperture of the ceramic membrane is precisely controlled, and the aperture is distributed in a gradient, which greatly accelerates the siphoning process and decomposition and diffusion process of organic matter. More importantly, the air circulation rate around the blank is greatly improved, the time required for degreasing is greatly shortened, and production efficiency is improved.

[0040] 2. The gradient porous ceramic membrane is used to achieve siphon degreasing and the powder embedding process is not used, which completely solves the technical problem of fine powder adhering to the surface of the blank. The production process eliminates the cleaning link and improves production efficiency.

[0041] 3. The porous ceramic membrane has high strength and can support the injection blank without collapse or deformation during the degreasing process, ensuring the consistency of the degreasing process and improving the yield rate of the degreasing blank.

[0042] 4. The size of the porous ceramic membrane can be designed according to the size of the kiln furnace. Multiple loading positions can be designed and processed on the same porous gradient ceramic membrane to place injection blanks to ensure the consistency of the same batch of degreased blanks, which is suitable for mass production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a physical picture of a single-layer through-hole ceramic membrane.

[0044] Figure 2 This is a physical picture of the gradient porous ceramic membrane.

[0045] Figure 3 Schematic diagram of the gradient porous ceramic membrane structure of the unprocessed stage.

[0046] Figure 4 Schematic diagram of the gradient porous ceramic membrane structure for processing the stage Figure 1 .

[0047] Figure 5 Schematic diagram of the gradient porous ceramic membrane structure for processing the stage Figure 2 .

[0048] Figure 6 TG-DSC test results for injection feeding.

[0049] Figure 7 It is the temperature curve diagram of the degreasing process of the embodiment and the comparative example.

[0050] Figure 8 This is a real picture of the injection blank before degreasing.

[0051] Fig. 9 The following are actual pictures of the apparent morphology of the degreased blanks of the embodiments and comparative examples. DETAILED DESCRIPTION

[0052] The present invention is further described below in conjunction with specific embodiments, but the methods and technical parameters involved in the scheme should not be understood as limitations of the present invention.

[0053] The embodiment of the present invention provides a method and process for rapid degreasing of a ceramic injection molded blank based on a gradient porous ceramic membrane.

[0054] Example 1

[0055] 1. Preparation of ceramic injection blanks:

[0056] (1) The basic composition of the ceramic feed is: 80wt% ZTA ceramic powder and 20wt% binder. The ZTA ceramic powder is composed of 68 parts of aluminum oxide, 30 parts of zirconium oxide, 1 part of magnesium oxide, 0.5 parts of titanium dioxide, and 0.5 parts of lanthanum oxide. The raw material powders are weighed in proportion and put into a ball mill with a material, ball, and water ratio of 1:2:2. The ball mill is milled at 60r / min for 24h. The slurry after ball milling is dried and granulated by spray granulation. After mechanical sieving, the ZTA ceramic powder used in this technical solution is obtained. 50 The binder is composed of 78% paraffin, 15% polyethylene glycol, 5% dibutyl phthalate, 1% stearic acid and 1% oleic acid.

[0057] (2) Feeding process: first add ZTA ceramic powder into the internal mixer and mix it by tumbling, gradually increase the temperature to 180°C, add the binder, and continue mixing for 2 hours. After mixing, the powder is extruded and pelletized to prepare feeding material for later use.

[0058] (3) Blank injection molding: The ZTA ceramic feed is placed in an injection molding machine and injected into the mold cavity at an injection pressure of 60 MPa and an injection temperature of 70°C. The ZTA ceramic injection blank is formed by cooling for 10 seconds. The injection blank is cylindrical with a diameter of 60 mm, a height of 10 mm, and a mass of 120 g.

[0059] 2. Preparation of gradient porous ceramic membrane:

[0060] For example, the preparation method of S1 in the technical solution prepares a ceramic membrane with a multi-level gradient pore size, and the pore size is 10μm, 120μm, 250μm, and 1000μm from top to bottom. The thickness of each layer of the ceramic membrane is 5mm, 10mm, 10mm, and 10mm from top to bottom.

[0061] 3. Degreasing process:

[0062] After weighing the ZTA ceramic injection blank, place it on the multi-level pore size ceramic membrane, set the degreasing process parameters, and perform degreasing. The degreasing process parameters are shown in the following table, and the heating stage takes 1480 minutes.

[0063] Temperature range time RT~120℃ 60min 120℃~240℃ 240min 240℃~300℃ 600min 300℃~460℃ 320min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0064] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, the weight of the degreased blank is 96.5g, and the degreasing rate is 97.9%. There are no wrinkles, cracks, bubbles and other defects on the surface that can be seen by the naked eye.

[0065] Example 2

[0066] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0067] 2. Preparation of gradient porous ceramic membrane:

[0068] For example, the preparation method S1 in the technical solution prepares a ceramic membrane with a multi-level gradient pore size, and the pore size is 50μm, 120μm, 250μm, and 1000μm from top to bottom. The thickness of each layer of the ceramic membrane is 5mm, 10mm, 10mm, and 10mm from top to bottom.

[0069] 3. Degreasing process:

[0070] After weighing the ZTA ceramic injection blank, place it on the multi-level pore size ceramic membrane, set the degreasing process parameters, and perform degreasing. The degreasing process parameters are shown in the following table, and the heating stage takes 1480 minutes.

[0071] Temperature range time RT~120℃ 60min 120℃~240℃ 240min 240℃~300℃ 600min 300℃~460℃ 320min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0072] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, the weight of the degreased blank is 98g, and the degreasing rate is 91.6%. There are a few wrinkles, bubbles and other defects on the surface.

[0073] Example 3

[0074] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0075] 2. Preparation of gradient porous ceramic membrane: The process parameters are consistent with those in Example 1.

[0076] 3. Degreasing process:

[0077] After weighing the ZTA ceramic injection blank, place it on the multi-level pore size ceramic membrane, set the degreasing process parameters, and perform degreasing. The degreasing process parameters are shown in the following table, and the heating stage takes 1180 minutes.

[0078] Temperature range time RT~120℃ 60min 120℃~240℃ 200min 240℃~300℃ 400min 300℃~460℃ 260min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0079] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, the weight of the degreased blank is 99g, and the degreasing rate is 87.5%. There are many defects such as wrinkles, bubbles and bubbling on the surface.

[0080] Example 4

[0081] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0082] 2. Preparation of gradient porous ceramic membrane: The process parameters are consistent with those in Example 1.

[0083] 3. Degreasing process:

[0084] After weighing the ZTA ceramic injection blank, place it on the multi-level pore size ceramic membrane, set the degreasing process parameters, and perform degreasing. The degreasing process parameters are shown in the following table, and the heating stage takes 1780 minutes.

[0085]

[0086] 300℃~460℃ 320min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0087] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, the weight of the degreased blank is 96.2g, and the degreasing rate is 99.1%. There are no wrinkles, bubbles or other defects on the surface.

[0088] Comparative Example 1

[0089] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0090] 2. Use powder embedding technology:

[0091] The buried powder material is high-temperature calcined α-Al2O3 particles with a particle d50 of 5μm. When burying the powder, first lay a layer of alumina powder in the alumina crucible with a thickness of about 20mm, place the injection blank, continue to add alumina powder, completely bury and cover the blank, and lightly compact the powder.

[0092] 3. Degreasing process:

[0093] The crucible is placed in the degreasing furnace as a whole. The degreasing process parameters are set and degreasing is performed. The degreasing process parameters are shown in the following table. The heating stage takes 1480 minutes.

[0094] Temperature range time RT~120℃ 60min 120℃~240℃ 240min 240℃~300℃ 600min 300℃~460℃ 320min 460℃~600℃ 140min 600℃~600℃ 120min 600℃~RT Natural cooling

[0095] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, the degreased blank is seriously sticky with powder, the mass of the surface layer after completely removing the thickness is 98 grams, and the degreasing rate is about 91.6%. The degreased blank with serious surface sticking powder cannot be used.

[0096] Comparative Example 2

[0097] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0098] 2. Use powder embedding technology:

[0099] The buried powder material is α-Al2O3 particles calcined at high temperature. 50=5μm. When burying powder, first lay a layer of alumina powder in the alumina crucible with a thickness of about 20mm, place the injection blank, continue to add alumina powder, completely bury and cover the blank, and lightly compact the powder.

[0100] 3. Degreasing process:

[0101] The crucible is placed in the degreasing furnace as a whole. The degreasing process parameters are set and degreasing is performed. The degreasing process parameters are shown in the following table. The heating stage takes 2840 minutes.

[0102] Temperature range time RT~120℃ 120min 120℃~240℃ 480min 240℃~300℃ 1200min 300℃~460℃ 640min 460℃~600℃ 280min 600℃~600℃ 120min 600℃~RT Natural cooling

[0103] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, and the surface of the degreased blank is sticky with powder. The mass after completely removing the surface layer is 96.5 grams, and the degreasing rate is about 97.9%. The surface of the degreased blank is sticky with powder, and there are a small amount of wrinkles and bubbles on the surface.

[0104] Comparative Example 3

[0105] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0106] 2. Use powder embedding technology:

[0107] The buried powder material is α-Al2O3 particles calcined at high temperature. 50 =5μm. When burying powder, first lay a layer of alumina powder in the alumina crucible with a thickness of about 20mm, place the injection blank, continue to add alumina powder, completely bury and cover the blank, and lightly compact the powder.

[0108] 3. Degreasing process:

[0109] The crucible is placed in the degreasing furnace as a whole. The degreasing process parameters are set and degreasing is performed. The degreasing process parameters are shown in the following table. The heating stage takes 3440 minutes.

[0110]

[0111]

[0112] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, and the surface of the degreased blank is sticky with powder. The mass after completely removing the surface layer is 96.5 grams, and the degreasing rate is about 97.9%. The surface of the degreased blank is sticky with powder, and there are a small amount of wrinkles and bubbles on the surface.

[0113] Comparative Example 4

[0114] 1. Preparation of ceramic injection blanks: The process parameters are consistent with those in Example 1.

[0115] 2. Use powder embedding technology:

[0116] The buried powder material is α-Al2O3 particles calcined at high temperature. 50 =10μm. When burying powder, first lay a layer of alumina powder in the alumina crucible with a thickness of about 20mm, place the injection blank, continue to add alumina powder, completely bury and cover the blank, and lightly compact the powder.

[0117] 3. Degreasing process:

[0118] The crucible is placed in the degreasing furnace as a whole. The degreasing process parameters are set and degreasing is performed. The degreasing process parameters are shown in the following table. The heating stage takes 3440 minutes.

[0119] Temperature range time RT~120℃ 120min 120℃~240℃ 480min 240℃~300℃ 1800min 300℃~460℃ 640min 460℃~600℃ 280min 600℃~600℃ 120min 600℃~RT Natural cooling

[0120] 4. After degreasing, take out the ZTA ceramic degreased blank, weigh it and observe its surface characteristics. The diameter of the degreased blank is 60mm, and the surface of the degreased blank is sticky with powder. The mass after completely removing the surface layer is 97.5 grams, and the degreasing rate is about 97.9%. The surface of the degreased blank is sticky with powder, and there are a small amount of wrinkles and bubbles on the surface.

[0121] In summary, for ZTA ceramic injection molded parts, the degreasing effects of the embodiments and comparative examples can be summarized as shown in the following table.

[0122]

[0123] According to the above table data and Fig. 9 The actual picture of the degreased blank shows that the comparative example adopts the siphon degreasing method of buried powder, and the better process parameters are the particle size d of the alumina powder. 50 The degreasing process parameters are as listed in Comparative Example 3, the heating stage takes about 3440 minutes, the degreasing rate is about 97.9%, and there is a small amount of sticky powder and wrinkles on the surface. The gradient porous ceramic membrane degreasing process is adopted, and all degreased samples have no carbon deposition phenomenon. The better process parameters are shown in Example 1, the heating stage takes about 1480 minutes, the degreasing rate is about 97.9%, and the surface quality is very good. The use of gradient porous ceramic membranes and optimized degreasing process parameters can not only ensure the quality of the degreased blanks, but also greatly improve the production efficiency of the degreasing process and the yield rate of the degreased blanks.

[0124] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for rapid degreasing of a ceramic injection molded blank, comprising: S1. Use template method to prepare porous ceramic membrane materials with precisely controllable pore size and pore size gradient distribution; S2. Make spatial modeling of the three-dimensional appearance of the injection blank, and according to the appearance of the blank, use mechanical processing methods to process a loading platform of the injection blank with a size and shape that precisely matches the blank, and then place the injection blank on the processed loading platform, and then match the precisely processed gradient ceramic membrane on top of the blank; the processing of the loading platform is limited to the ceramic membrane layer with the smallest pore size to ensure that the surface of the injection blank is in direct contact with the membrane layer with the smallest pore size of the ceramic membrane; the composition of the ceramic injection blank: the basic composition of the ceramic feed is: 80wt% ZTA ceramic powder and 20wt% binder; the composition of the ZTA ceramic powder is: 68 parts of aluminum oxide, 30 parts of zirconium oxide, 1 part of magnesium oxide, 0.5 parts of titanium dioxide, and 0.5 parts of lanthanum oxide; the composition of the binder is: 78% paraffin, 15% polyethylene glycol, 5% dibutyl phthalate, 1% stearic acid, and 1% oleic acid; S3. Perform TG-DSC analysis on the ceramic injection feed and design accurate degreasing process parameters based on the TG-DSC analysis results; S4. Set the temperature curve of the debinding furnace according to the designed debinding process parameters to quickly complete the debinding process in an air atmosphere; S5. After degreasing, the injected ceramic blank is taken out, the degreasing blank is weighed, its surface characteristics are observed and recorded, and the degreasing effect is evaluated; wherein: The porous ceramic membrane material in step S1 is prepared by the following method: (S1-1) Preparation of alumina ceramic slurry: α-alumina powder and magnesium oxide powder are mixed and placed in a ball mill of a horizontal ball mill, with alumina ceramic balls as grinding media and pure water as dispersion medium. 0.1% triethanolamine is added according to the mass of the mixed powder, and the mixture is fully ball-milled to obtain a ceramic slurry for use; (S1-2) Organic template pretreatment: placing the polyurethane foam in a 10% by mass NaOH solution, heating and soaking it in a water bath, rubbing and washing it, and then drying it to obtain a pretreated polyurethane foam; (S1-3) Dipping and slurrying: the pretreated polyurethane foam is placed in the ceramic slurry of step (S-1) for dipping and slurrying, and the process is repeated three times, and the excess ceramic slurry is removed by a roller press to obtain the slurry-coated polyurethane foam; (S1-4) Laminating and drying: Laying the slurry polyurethane foam in layers, applying a small amount of carbon powder particles between the layers, and drying in an oven to obtain a laminated body; (S1-5) debinding: placing the dried laminated green body into a debinding furnace, gradually heating it to 500-650° C. and keeping it warm, to obtain a debinding green body; (S1-6) Sintering: The debinding green body is placed in a kiln, gradually heated to 1400-1450°C for insulation, and then cooled naturally to obtain a porous ceramic membrane material; In step S2, the pore size range of the gradient porous ceramic membrane is 0.1 mm to 1.2 mm; The aperture gradient size is designed as 0.1~0.2mm for the innermost layer, 0.5~0.6mm for the middle layer, and 1~1.2mm for the outermost layer; The film thickness is 6 to 12 times the thickness of the blank; The degreasing process parameters in step S4 include: 。 2. The rapid degreasing method according to claim 1, wherein: The mass ratio of the α-alumina powder to the magnesium oxide powder in step (S1-1) is 99:1; The mass ratio of material, ball and water is 1:5:2; The rotation speed of the ball mill is 60 r / min, and the ball milling is performed for 24 hours.

3. The rapid degreasing method according to claim 1, wherein: The water bath heating temperature in step (S1-2) is 60° C. and the soaking time is 4 h; The drying temperature is 60-110° C., and the drying time is 8-12 hours.

4. The rapid degreasing method according to claim 1, wherein: The oven temperature in step (S1-4) is 80-110°C and the drying time is 8-12h.

5. The rapid degreasing method according to claim 1, wherein: The heating rate in step (S1-5) is 2°C / min and the insulation time is 1-2h.

6. The rapid degreasing method according to claim 1, wherein: The heating rate in step (S1-6) is 5°C / min and the insulation time is 1-2h.